Types of figurative language found in bon jovi song lyrics - Lembu, Eufronius Sarino; Pratiwi, Desak Putu Eka; Candra, Komang Dian Puspita (Journal of Language and Applied Linguistics, 2022)
This study aim to analysis types Figurative language and their meaning found in Bon Jovi song lyrics. In every song we can find many languages that contain figurative language because that’s the important element in the song to deliver the meaning to the listener. `The data source of this study were taken from https://w.azlyrics.com/ which consists of several lyrics that taken by the researcher. The data were collected used the observation method. Whereas the descriptive qualitative method was used to analyse the data in this study. The data were analysed base on theory of figurative language by Knickerbocker and Reninger (1963) and the meaning used the theory by Barthes (1964). The finding of the study analysis 10 types of figurative language base on the song from 2 albums of Bon jovi song lyrics such as 4 types of similes ,1 types of metaphors ,2 types of , 1 type of metonymy ,9 types of hyperboles ,2 types of irony,1 type of allusion 1 type of paradox with the percentage unfortunately, the writer didn’t dead metaphor and Synecdoche in the song lyrics. The types of figurative language contain with the denotative and connotative meaning.